2008
DOI: 10.1177/0263276408095544
|View full text |Cite
|
Sign up to set email alerts
|

Conjugating the Modern/ Religious, Conceptualizing Female Religious Agency

Abstract: This article is concerned with thinking transformations of the secular, and does so in relation to two theoretical terrains, while empirically grounded in ethnographies of Christian and Islamic pious women in the Netherlands. A first theoretical terrain under consideration is that of how the relation between modernity and religion is elaborated, notably in secularization theories, and how these established frameworks are challenged by a different kind of articulation between modernity and religion that I obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
107
0
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(118 citation statements)
references
References 15 publications
1
107
0
10
Order By: Relevance
“…Mahmood's perspective has been crucial to theorizing women's piety in the Arab world but also in Europe and South East Asia (jacobsen, 2006;Jouili, 2006;Minganti, 2007;Scott, 2007;Bracke, 2008;Fadil, 2008;Turner and Tong, 2008). A central concern to Mahmood (2001aMahmood ( , b, 2003Mahmood ( , 2005 is that the liberal-progressive agenda undergirding feminist theorizing on freedom, agency and the human subject limits the ability to comprehend women's piety in its complexity.…”
mentioning
confidence: 99%
“…Mahmood's perspective has been crucial to theorizing women's piety in the Arab world but also in Europe and South East Asia (jacobsen, 2006;Jouili, 2006;Minganti, 2007;Scott, 2007;Bracke, 2008;Fadil, 2008;Turner and Tong, 2008). A central concern to Mahmood (2001aMahmood ( , b, 2003Mahmood ( , 2005 is that the liberal-progressive agenda undergirding feminist theorizing on freedom, agency and the human subject limits the ability to comprehend women's piety in its complexity.…”
mentioning
confidence: 99%
“…In doing so, Mahmood convincingly demonstrated that pious women's appropriation of religious concepts in fact contains a particular form of agency that had previously been neglected by feminist theory. Her ground-breaking work triggered a post-secular diversion in the ontology of feminist agency as it forced feminist theorists to question the limits of feminist thinking in realms of piety (Bracke 2008;Braidotti 2009) and contributed to post-colonial feminist theory.…”
Section: Women's Political Agency During Islamic Revivalismmentioning
confidence: 99%
“…Such a secular liberal view has been challenged on grounds of a postcolonial ethnocentrism that frames pious Muslim women as the Other of an autonomous Eurocentric subject. Another line of theory, which from here on I will call the 'doing religion' paradigm (Avishai, 2008) put forth the idea that women comply with and participate in conservative religions for the sake of religious ends only rather than any other gains (Avishai, 2008;Bracke, 2008;Mahmood, 2005;Jacobsen, 2011), with a view to 'doing religion'; 'as a mode of conduct and being' (Avishai, 2008, p. 412).…”
Section: Theorizing Handshaking and Agencymentioning
confidence: 99%